The Relationship between Market Orientation and Business Performance in Manufacturing Industry: The Mediating, Green Economy Strategy and Moderating, Dynamic Capabilities and Socially Responsible Leadership - Phongphanich, Nara; Chimpleewat, Kritsada; Lalaeng, Chanyaphak (Journal of Ecohumanism, 2025)
Objectives: The purpose of this study is to examine the relationship between a market orientation that influences green economy strategies and the businesses performance in Thailand manufacturing industry. It also explores the role of mediating variables such as green economy strategies and moderating variables socially responsible leadership and dynamic capabilities. Methods: The population used in this study was a group of 622 businesses in the Thailand’s manufacturing industry that have been certified to ISO 14001 environmental standards, a sample of 320 (Wiratchai, 1999). Using the PLS model, a three-stage approach was used for direct path, mediation effect analysis, and moderation effect analysis. Results: Green economy strategy (GES) has a direct positive effect on business performance (BP), Market orientation (MO) has a direct positive effect on business performance (BP), Market orientation (MO) has direct impact green economy strategy (GES), Dynamic capabilities (DC) has direct impact business performance (BP), Socially responsible leadership (SRL) has a direct impact green economy strategy (GES), Market Orientation (MO) impact business performance (BP), Dynamic capabilities (DC) has no influence on the relationship between green economy strategy (GES)and business performance (BP), and Socially responsible leadership (SRL) has no influence on the relationship between market orientation (MO) and green economy strategy (GES) Conclusions: In light of these findings, we discuss the theoretical and practical implications, limitations of the study. This study underscores the importance of green economy strategy contribute to business performance. Including causal factors that affect corporate green economy strategy.